From Transcultural Entanglements to Integrated Learning Experiences? Transcultural Museum Education at Berlin's Museum of Islamic Art - Lӧseke, Annette (Revija za elementarno izobraževanje, 2022)
Taking three educational initiatives at the Museum of Islamic Art in Berlin as case studies, this paper explores how the museum engages in transcultural museum education. While the exhibition parcours 'Objects in Transfer' highlights the transcultural entanglements of objects, 'Multaka' is a traineeship project preparing refugees from Syria and Iraq to become museum tour guides for Arabic-speaking visitors. 'Tamam', a joint initiative with mosque communities and Muslim associations across Germany, develops collection-centred educational material for young Muslims. The paper explores key findings from an evaluation of the interactive exhibition parcours 'Objects in Transfer' within the context of collaborative initiatives such as 'Multaka' and 'Tamam'.
Keywords: transcultural intertwining, museum education,exhibition parkour